Investment preparedness for carbon trading in Kenya’s arid and semi-arid lands: Perspectives from Turkana County - Jalango, Dorcas; Omala, Millicent (2025)
This report presents the outcomes of a Carbon Market Readiness and Investment Opportunities Workshop convened by the Turkana County Government in partnership with the Alliance of Bioversity International and CIAT under the AICCRA project. The workshop enhanced understanding of carbon markets, strengthened capacity to design viable carbon projects, and informed policy alignment for integrating carbon finance into county planning. Five project concepts—agroforestry, biochar, biogas, clean cooking, and rangeland restoration—were developed, highlighting Turkana’s potential in climate action and green investment. The report outlines key findings, policy recommendations, and next steps toward implementing a credible, community-driven carbon portfolio.